Chimpanzee and felid diet composition is influenced by prey brain size. - Shultz, S; Dunbar, R (2006)
Prey use a wide variety of anti-predator defence strategies, including morphological and chemical defences as well as behavioural traits (risk-modulated habitat use, changes in activity patterns, foraging decisions and group living). The critical test of how effective anti-predator strategies are is to relate them to relative indices of mortality across predators. Here, we compare biases in predator diet composition with prey characteristics and show that chimpanzee (Pan troglodytes) and felid show the strongest and the most consistent predator bias towards small-brained prey. We propose that large-brained prey are likely to be more effective at evading predators because they can effectively alter their behavioural responses to specific predator encounters. Thus, we provide evidence for the hypothesis that brain size evolution is potentially driven by selection for more sophisticated and behaviourally flexible anti-predator strategies.